Task, formulaic language, and role play for developing ESL students’ academic language - Rajeswaran, Chandrasena Mandalasamy (Indonesian Journal of Applied Linguistics, 2019)
The effectiveness of task, formulaic language, and role play in facilitating uninhibited communication of ESL learners is beyond doubt. This quantitative empirical research employed a role play communicative assessment and a writing assessment to assess the efficacy of the combination of task, formulaic language, and role play, as a language learning strategy to teach cognitive academic language in English for Specific Purpose classroom of a university. The language ability acquired through brainstorming and reading sessions equipped the students for the task of describing a two-wheeler. The task which made use of the formulaic language led the engineering students to interact meaningfully and know the content for describing a two-wheeler and write the description in a coherent paragraph. The stimulated usage of academic language in a role play could scaffold the content and language learnt for successful retention for effective Oral Academic Presentation (OAP). Although the results cannot be generalised, students joining higher education in universities in ESL/EFL countries would be immensely benefitted by this kind of teaching method.